A guava pulp composition. - Ismail, Amin (2011)

(untitled)
The present invention discloses a guava pulp (also referred to as pulp composition)of a particle size not greater than 0.25 mm which does not contain seeds and peels from the guava and has a lycopene which is 1 to 2 folds higher than the lycopene concentration in the guavas from which the pulp is obtained. The invention further discloses uses of the pulp compositin as starting material for obtaining guava oleoresin and lycopene, and as antioxidant.